What times should be used for fNIRS and EEG protocol? - Ribeiro, Iara Margolis (2023)
fNIRS (Functional near-infrared spectroscopy) and EEG (Electroencephalogram) are two technologies that measure brain activity. Recently expanded to new fields, such as Design. These technologies are beginning to be applied simultaneously in the laboratory or in real life, as they allow researchers to collect distinct data - electrical activity in the form of brain waves and the concentration of oxygenated and deoxygenated hemoglobin (HbO and HbR), respectively. The purpose of this study is to present a review on the event timing applied individually to optimize the usage of both tools, and a reflection on how a study protocol should be designed for the integration of both technologies into a hybrid fNRIS-EEG recording. The results show that the purpose of the study and the type of stimulus or task to be done by the participants, must be considered since they determinate the events timing in each step of the protocol. Event timing includes longer durations when there is interaction between the participant and the stimulus, or for completion of a task. Additionally, the resting period for fNIRS signals baseline correction must be carefully considered for the convergence on the use of both technologies in the same protocol.